2014
DOI: 10.1080/19371918.2014.969860
|View full text |Cite
|
Sign up to set email alerts
|

An Ecological Perspective on Rural, Low-Income Mothers' Health

Abstract: Using structural equation modeling, this study examined interactions among factors traditionally associated with health outcomes within a sample of rural low-income mothers. Prior research has established that education, employment, income, marital status, and health insurance coverage independently predict health outcomes. However, no studies have examined the simultaneous influence of these factors as conceptualized from an ecological systems perspective. Results indicate that when the multiple factors are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Rural communities tend to have limited health care resources, and their residents frequently experience barriers to health information and care (Bice‐Wigington, Simmons, & Huddleston‐Cassas, ; Smalley et al., ). This study suggests that rural women are engaging in multiple unhealthy behaviors that increase their risk for cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Rural communities tend to have limited health care resources, and their residents frequently experience barriers to health information and care (Bice‐Wigington, Simmons, & Huddleston‐Cassas, ; Smalley et al., ). This study suggests that rural women are engaging in multiple unhealthy behaviors that increase their risk for cancer.…”
Section: Discussionmentioning
confidence: 99%
“…This study revealed that single mothers already assumed more than half of the workload in many aspects of family role responsibilities prior to the pandemic, but that shutdowns exacerbated their disproportionate family responsibilities. The interrelated challenges due to loss of childcare, schooling, and jobs exacerbated family responsibilities ( Bice-Wigington et al, 2015 ). The long-term consequences of these disproportionate challenges are not yet known for single mothers.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies suggest that persons with low-SES (socioeconomic status) backgrounds are more likely to smoke, be obese, and not exercise regularly (Bice-Wigington, Simmons, & Huddleston-Casas, 2015). Our findings were in keeping with the previous literature.…”
Section: Discussionmentioning
confidence: 99%